La guerra de la Independencia en la dramaturgia chilena del siglo XIX - Faúndez Carreño, Tania (2024)
War has become a constant theme in Chilean drama, which in turn has been closely linked to national identity. The pulsion of war, with its institutional discursive mechanisms (historical, political, cultural, military, national), its undulations, and the difficulty of representing it on stage have resonated in Chilean dramaturgy since the consolidation of the Republic in the nineteenth century (1817) until the tremendous celebration of the national Bicentennial (2010). Our study examines how war impulse (during the pre-war, war and post-war periods) have been embedded in the war drama of the XIX century. For this, we will analyze three texts: La Camila o La patriota de Sud-América (1817), by Camilo Henríquez, La hija del Sur o La Independencia (1823), by Manuel Magallanes and Ernesto (1842), by Rafael Minvielle. In these dramas, we will observe the relationship between war and theater, and how the warlike pretext appears (action, historical context, background, or political, economic, and social dimension) in works with some representative importance in the national theater scene.